MANAJEMEN RISIKO KREDIT BERMASALAH PADA BANK BJB KANTOR CABANG SOREANG - Abielya Steffina Nasyachril; Areilya Stefhany Nasyachri; Rita Zulbetti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to find out the risk management that occurs in the field of credit lifeinsurance, the level of collectibility of bad credit, as well as procedures applied bybank bjb soreang branch office in case of some obstacles experienced by the debtorin paying the agreed insurance premium. By using qualitative descriptive researchthat analyzes existing events or problems. The data obtained in the form of secondarydata from the consumer policy nominative report in 2020. Data collection techniquesin the form of field observation by conducting interview activities on the mattersneeded with related parties. There are 2 data obtained, namely consumer policynominative data in 2020 in may and july that experienced bad credit. The method ofcalculating non-performing credit analysis using npl formula in accordance with sebi no. 21/11/dndp/2010. The result of the calculation is in may of 0.026% and july0.017%, the npl is still within reasonable limits and is said to be healthy notexceeding the maximum npl limit set by bi of 5%.